Pengembangan Game untuk Kasus Verbal Bullying di Kalangan Remaja Sekolah - Istihar Bahi fajar; Muhammad Andik Izzudin; Subhan Nooriansyah (CV. Creative Tugu Pena, 2024)
The development of games for verbal bullying cases is important as education for school adolescents. The system is carried out by integrating game elements to increase the Usability of school adolescents. This study aims to simulate and understand cases of verbal bullying among school adolescents through the development of game systems and then testing the effectiveness of the game using the System Usability Scale (SUS) method. The game system is carried out by integrating game elements to increase the motivation and involvement of school adolescents in the learning process. With the system developed using the ADDIE model can help the process to completion through 5 stages. The results of the implementation were tested using the SUS method to measure usability and functionality. The average test score using the SUS method reached 83.75. This score indicates that the majority of users feel that the system has good usability and is sufficient in supporting their gaming experience. The distribution of these scores gives a clear picture of how the system was received by the users and shows that the system as a whole has a high level of usability. Hence the conclusion that the game created for verbal bullying was successful.